Syntheses, Characterizations, and Inhibition Activities Against Coxsackievirus B3 of Iodobenzoic Hydrazide Functionalized Hexamolybdates - Wang, Long-Sheng; Guo, Chao; Hu, Da; Zhao, Yan-Xi; Liu, Hui-Hui; Dong, Yu-Jia; Sun, Shang-Bin; Liu, Xing; Hu, Kang-Hong; Wei, Yan-Hong (Frontiers in Chemistry, 2022)
A class of iodobenzoyldiazenido functionalized POMs, (TBA)3[Mo6O18(=N=NCOAr)] (Ar = Ph-o-I (1); Ph-m-I (2); Ph-p-I (3); Ph-3,4-I2 (4); Ph-3,4,5-I3 (5) (TBA = tetrabutyl ammonium) are prepared via the refluxing reaction of α-octamolybdates, DCC and corresponding hydrazides in dry acetonitrile. Their structures were determined by FT-IR, UV-Vis spectra, 1H NMR and HR MS. Research on biological activity of title compounds shows L3, L5, 3 and 5 demonstrate potent inhibitory activity against Coxsackievirus B3 (CVB3) and low in vitro cytotoxic activity against Hep-2 cell lines. The covalent linkage between the iodobenzoyldiazenido components and POMs can enhance the molecular inhibitory efficiency of iodobenzoyl hydrazides.